Implementation of Satellite Payload Program Reconfiguration on Low-Cost SDR - Fadilah, Nurul; Pratomo, Bina; Muhtadin, Nurul; Soedjarwo, Moedji (Jurnal Teknologi Dirgantara, 2022)
A software-defined radio (SDR) is a radio communication system that uses reconfigurable software-based components for digital signal processing and conversion. These radio devices, in contrast to typical radio communication systems, are extremely adaptable and versatile. This technology has recently been implemented in CubeSat payloads for connecting the continuously expanding wireless world. SDR devices provide flexibility and versatility by allowing the payload configuration and application to be modified in orbit. This study presents the concept and implementation of an SDR ground simulator utilizing inexpensive hardware rather than a typical computer. The simulator runs on Raspberry Pi hardware with Linux OS and is written in the Phyton programming language. This work presents a model and algorithm of satellite software reconfiguration implemented in the SDR hardware ground simulator. The concept is simple and easy to implement and is potentially useful to be used in future satellite missions